2003
DOI: 10.1051/gse:2003038
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of 52 chicken populations assessed by microsatellite typing of DNA pools

Abstract: -In a project on the biodiversity of chickens funded by the European Commission (EC), eight laboratories collaborated to assess the genetic variation within and between 52 populations from a wide range of chicken types. Twenty-two di-nucleotide microsatellite markers were used to genotype DNA pools of 50 birds from each population. The polymorphism measures for the average, the least polymorphic population (inbred C line) and the most polymorphic population (Gallus gallus spadiceus) were, respectively, as foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
119
6
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(143 citation statements)
references
References 19 publications
15
119
6
3
Order By: Relevance
“…Lower values than the results found in this study were also described by AL-QAMASHOUI et al (2014) - 8.4 (VANHALA et al, 1998;KYSER et al, 2000;ZHANG et al, 2002;HILLEL et al, 2003;TADANO et al, 2007;BERTHOULY et al, 2008;ROSÁRIO et al, 2009;CHATTERJEE et al, 2010;TADANO et al, 2012;WILKINSON et al, 2012). Normally, it is expected that the genetic variability of commercial chickens lines had been reduced because they are selected for quantitative traits (HILLEL et al, 2003). However the average number of alleles to PP and RN lines, especially when compared to commercial birds, indicates that there were no lost in the genetic variability in the raise of these lines, originally found in their free range chickens ancestors.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…Lower values than the results found in this study were also described by AL-QAMASHOUI et al (2014) - 8.4 (VANHALA et al, 1998;KYSER et al, 2000;ZHANG et al, 2002;HILLEL et al, 2003;TADANO et al, 2007;BERTHOULY et al, 2008;ROSÁRIO et al, 2009;CHATTERJEE et al, 2010;TADANO et al, 2012;WILKINSON et al, 2012). Normally, it is expected that the genetic variability of commercial chickens lines had been reduced because they are selected for quantitative traits (HILLEL et al, 2003). However the average number of alleles to PP and RN lines, especially when compared to commercial birds, indicates that there were no lost in the genetic variability in the raise of these lines, originally found in their free range chickens ancestors.…”
Section: Resultscontrasting
confidence: 56%
“…CLEMENTINO et al (2010) andFONTEQUE et al (2014) found an average number of 9.6 and 12.4 alleles per locus, respectively, in studies with microsatellites in free range chickens from Brazil. Lower values than the results found in this study were also described by AL-QAMASHOUI et al (2014) - 8.4 (VANHALA et al, 1998;KYSER et al, 2000;ZHANG et al, 2002;HILLEL et al, 2003;TADANO et al, 2007;BERTHOULY et al, 2008;ROSÁRIO et al, 2009;CHATTERJEE et al, 2010;TADANO et al, 2012;WILKINSON et al, 2012). Normally, it is expected that the genetic variability of commercial chickens lines had been reduced because they are selected for quantitative traits (HILLEL et al, 2003).…”
Section: Resultscontrasting
confidence: 53%
“…Local chicken breeds are resilient to harsh environmental conditions, are bred for disease resistance and are easy to raise (Pinard- Van Der Laan et al, 1998). The origin of modern domestic chicken has been well investigated during the last decade (Berthouly et al, 2008;Granevitze et al, 2007;Hillel et al, 2003;Muchadeyi et al, 2007;Pinard-Van Der Laan et al, 1998). In this paper, we conducted an mtDNA control region sequences polymorphism analysis in Jiangxi, China.…”
Section: Discussionmentioning
confidence: 98%
“…Among molecular markers, microsatellites were preferred because they are well dis-persed in the genome and highly polymorphic (Cheng et al, 1995). They have been used in many countries to study the genetic relationships among local breeds (Takahashi et al, 1998;Hillel et al, 2003;Baumung et al, 2004;Muchadeyi et al, 2007;Dalvit et al, 2009), and their use allows meta-analysis and comparisons among independent research units.…”
Section: Introductionmentioning
confidence: 99%